Some Rare and Imperfectly Known Medicinal Plant Species of Uttaranchal - Chandola, S. (Indian Forester, 2005)
Valuable species have been removed for so long and so intensively from the wild that they have come to the brink of extinction. The market forces, however have heen so strong that substitutes have emerged to satisfy the demand, and over time the substitute has assumed the importance of the original drug. The present paper deals with correct identity of Akarkara (Anacyclas pyrethrum), Chirayta (Swertia chirata), Kuth (Saussurea costus), Salam Mishri (Eulophia dabia). Gentiana kurroo has been rediscovered after a lapse of 50 years. It is timt~ now to educate ourselves and to adopt the latest benefits of modern science to retrieve the true herbs spccies from final annihilation. Serious Species Recovery Programmes need to be initiated for the highly threatened plants.